Determining the reliability level by combining FMEA, FTA and dematel tools - Bujna, Marián; Prístavka, Miroslav; Lee, Chia Kuang; Strápeková, Zuzana; Kapela, Krzysztof; Malicevic, Zoran (Sciendo, 2024)
The aim of the paper was to determine the level of reliability of a carousel type device. Considering the improvement of reliability, we decided to use the basic tools of FMEA and FTA. Using FMEA, we identified the most critical part of the equipment, namely welding (RPN=320). The proposed measure only solved the improvement of detection. Based on the FMEA analysis, we chose the TOP event for FTA - bad weld. The detected probability of peak event failure by quantitative FTA analysis was at the level of 0.58%. We identified the basic events leading to the TOP event, i.e. an allowed sonotrode, incorrect position of the membrane during sampling, short welding time and insufficient weld depth. Subsequently, reliability indicators were quantified. We achieved almost 100% availability values. Despite this, the aim was to find out a more comprehensive level of reliability and follow up findings from FMEA. We used the DEMATEL model and our own proposed economic model. Using the DEMATEL model, we found out that short welding time and an insufficient weld depth are the causative modes, that means, they significantly influence other failure modes and do so with a high significance. The creation of an economic evaluation model based on the quantification of direct costs for failure modes with the consequences of a certain number of defective products contributed to the fact that we again determined that the failure modes short welding time and insufficient depth are the modes with the highest priority for solving the bad weld event. The costs incurred as a result of their occurrence and as a result of the occurrence of downtime were the highest with these regimes. These models create space for us to more effectively design measures to improve the level of reliability and production quality, what is a prerequisite for ensuring a reduction in downtime, an increase in production quality and reliability, and an overall cost reduction. This also leads to an increase in the reputation of manufacturers.